Neurocognitive Functioning of Patients with Sinonasal and Nasopharyngeal Cancers Treated With Multimodality Therapy - Yaniv, Dan; Niccolai, Lindsay M.; Wefel, Jeffrey S.; Sullaway, Catherine M.; Phan, Jack; Fuller, Clifton David; Haroun, Kareem B.; Hanna, Ehab Y.; Su, Shirley Y. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Importance Few recent studies have examined neurocognitive functioning (NCF) in patients with sinonasal and nasopharyngeal cancers (NPCs) prior to and following multimodality therapy or the potential differences in NCF by disease variables such as disease site.Objective The objective of this study is to determine rates of NCF impairments prior to and following multimodality therapy, declines in NCF following radiotherapy (RT), and possible differences in NCF by the disease site.Design, Setting, and Participants We conducted a retrospective chart review of 39 patients with sinonasal and NPCs who underwent comprehensive neuropsychological evaluations. Twenty patients were evaluated prior to RT, of which eleven received follow-up evaluation after completion of RT. Nineteen patients were evaluated following various treatments without a pre-RT evaluation.Main Outcomes and Measures Patients completed comprehensive neuropsychological evaluations. Decline from pre-RT to follow-up was defined on the basis of reliable change indices.Results Thirty-nine patients completed comprehensive neuropsychological evaluations. For the entire cohort, the most frequently demonstrated impairments were in verbal memory (47%) and learning (43%), executive functioning (33%), and verbal fluency (22%). At post-RT follow-up, the most frequently observed declines were in verbal learning (46%) and memory (18%). Demographic and disease variables were not significantly associated with NCF at pre-RT or post-RT.Conclusion and Relevance Patients with sinonasal and NPCs are at risk for NCF impairments in multiple areas at baseline and memory decline following RT. Future prospective studies are needed to investigate the impact of each treatment modality on NCF and specific risk factors for cognitive dysfunction.
Keywords: executive functioning; radiotherapy; cognitive impairment; chemotherapy